Prevalance and association of Helicobater Pylori with gastro-duodenal mucosal lesions in patients with dyspepsia - Siddique, Abu Raihan; Hossain, Liakat; Rana, Mushtaque Ahmad; Banerjee, Probir Kumar; Rahman, Anisur; Chowdhury, Md Asraf Uddin; Sina, Hashmi; Yeasmin, Sabiha; Siddique, Abu Tanvir (Journal of Dhaka Medical College, 2020)
Helicobacter Pylori a very common worldwide infection is responsible for number of upper GIT lesions like gastritis, peptic ulcer disease, gastric carcinoma and mucosa associated lymphoid tissue lymphoma. On the other hand, dyspepsia is a wide spectrum of nonspecific upper GIT symptoms for which patients very frequently visit gastroenterology clinics. The objective of the study was to find prevalence of Helicobacter Pylori among the patients with dyspeptic symptoms who had gastro-duodenal mucosal lesions on upper GIT endoscopy and also if there is any association between these two variables. 164 cases of dyspepsia were done index upper GIT endoscopy as per inclusion and exclusion criteria from April 2018 to December 2018 in Seikh Sayera Khatun Medical College Hospital, Gopalganj. Two gastric biopsies (from antrum and body) were taken and immediately placed in a commercial RUT (rapid urease test) kit. Positive test (rapid urease test) was indicated by change in the color of the kit from yellow to pink or red within 24 hours. Out of 164 patients, 62 (37.8%) patients had gastro-duodenal mucosal lesions and rest(62.2%) showed normal upper GIT at endoscopy. Among the 62 patients highest (38) number of the patients endoscopy showed gastritis and least (3) showed gastric ulcer. Among 62 patients with endoscopic gastro-duodenal mucosal lesions, 36 patients were infected with Helicobacter Pylori. On the contrary 27 patients out of 102 subjects who had normal upper GIT at endoscopy recorded infected with Helicobacter Pylori. Statistically analysis was done using chi-square test with the help of SPSS software windows version 25. The level of statistical significance was set at 0.05. In our study it was observed that statistically there was significant relation of Helicobacter Pylori with gastro-duodenal mucosal lesions as P value was less than 0.05. In this study, we found that Helicobacter Pylori was significantly associated with gastro-duodenal mucosal lesions among the patients with dyspeptic symptoms. So, our suggestion will be to confirm H. pylori infection if anybody has gastro-duodenal mucosal lesions if a subject does upper GIT endoscopy for dyspeptic symptoms. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 100-104